Wide-Awake Wrist Arthroscopy and Open TFCC Repair - Hagert, Elisabet; Lalonde, Donald H. (Journal of Wrist Surgery, 2012)
The wide-awake approach to hand surgery entails the use of local infiltration anesthesia using lidocaine with epinephrine and no tourniquet. The technique provides practitioners with an option to perform advanced hand surgical care in an ambulatory setting, without the need for general or regional anesthetics. We present our results using wide-awake approach in wrist surgery, both open and arthroscopic. Between June and August 2011, the wide-awake approach was used in nine elective wrist surgery cases; three arthroscopic procedures, four open triangular fibrocartilage complex (TFCC) repairs, and two combined arthroscopy/open surgery (eight men/one woman). The arthroscopic patients were anesthetized using dorsal infiltration of lidocaine with epinephrine (20 mL) with an additional intra-articular 5 mL injection 30 minutes before surgery. The open surgery patients received 40 mL of lidocaine with epinephrine around the ulnar aspect of the forearm, from 8-cm proximal to 3-cm distal to the distal radioulnar joint. Standard diagnostic radio- and midcarpal arthroscopies were performed, where one patient had a loose body removed and two patients underwent TFCC debridements due to central TFCC tears. The six open cases were all due to TFCC foveal disruptions, which were reinserted using osteosutures in the distal ulna. Following placement of the ligament sutures, a preliminary knot allowed active and passive motion testing of pronosupination, to determine the adequate amount of tension in the ligaments. The wide-awake approach to wrist surgery is a plausible and reliable technique that eliminates the need for general anesthesia, removes the need of a tourniquet, and provides a cost-efficient and safe approach to wrist surgery. The ability to control ligament reconstructions using active motion may additionally enhance the rehabilitation of these patients, both through early proprioceptive awareness and adequate tensioning of soft tissues.
Keywords: arthroscopy; local anesthesia; proprioception; TFCC; wide-awake surgery; wrist